Writing in Learning Mathematics and Problem Posing Approach - Lutfi, Ahmad; Forkpah, Eric (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa Tanah Datar Sumatera Barat, 2024)
Solving math problems through writing not only deepens their understanding of mathematics but also strengthens their communication skills about mathematics and learning vocabulary in mathematics lessons, because writing means they can explain what they have done and why the strategy works. Mathematics learning should provide space and opportunities for children to ask questions, by formulating their own questions from given mathematical situations or related to material in mathematics. This can be accommodated by learning using the Problem Posing approach. This research aims to discuss the relationship between writing in mathematics and the problem posing approach. This type of research is qualitative descriptive research with a literature study method. Data was collected through related journals for study. The research results show that learning activities must be able to develop various students' mathematical abilities. Based on the explanation given, one alternative learning strategy that can develop students' mathematical abilities is the Writing in Learning Mathematics strategy and learning by problem posing.